An Optometrist-Led Eye Care Program for Older Residents of Retirement Homes and Long-Term Care Facilities - Labreche, Tammy (Canadian Geriatrics Society, 2011)
BACKGROUND AND PURPOSE: Visual impairment among older adults residing in long-term care (LTC) facilities and retirement homes is common and can have a significant adverse impact on their quality of life. Despite the burden of illness, they frequently receive inadequate eye care. We describe an optometrist-led eye care program serving this population, including a profile of participants and the program’s educational role for optometry students. METHODS: An optometrist assessed residents of LTC facilities and retirement homes. Participants received their routine eye care, which included a report to the resident’s family physician, through the program. A chart review was conducted for a consecutive series of patients; data were recorded on a standardized data abstraction form. RESULTS: All residents examined had at least one (average 1.8) ocular condition. Challenges presented by residents in their assessment, such as confusion and/or impaired comprehension (14.3%), refusal or poor cooperation (13.2%), and physical limitations (8.8%), were common, indicating the necessity of adapting eye assessment procedures to the needs of this population. CONCLUSION: This study supports the involvement of optometrists in the eye care for residents of retirement homes and LTC facilities, where optometrists can be an important clinical and educational resource. The program is a useful learning opportunity for optometry students.